Identifying Essential Components of a Digital Health Innovation Ecosystem for the Namibian Context: Findings from a Delphi Study. Issue 1 (5th December 2017) - Iyawa, Gloria Ejehiohen; Herselman, Marlien; Botha, Adele
Abstract: The concept of digital health innovation ecosystems is an emerging body of literature which suggests that components of digital health, innovation and digital ecosystems are important in the administration and delivery of healthcare services. The current literature indicates which components of digital health, innovation and digital ecosystems constitute a digital health innovation ecosystem, but it is less clear as to which components of digital health, innovation and digital ecosystems are relevant to the development of such an ecosystem for the Namibian context. The purpose of this paper was to identify the components of digital health, innovation and digital ecosystems relevant to the development of a digital health innovation ecosystem for the Namibian context. Therefore, the Delphi method was adopted in which 22 knowledgeable professionals from within the Namibian context were purposively selected to take part. The findings revealed essential components of digital health, innovation and digital ecosystems which are considered relevant to the development of a digital health innovation ecosystem for the Namibian context. Additionally, there are differences noted between the components of digital health, innovation and digital ecosystems essential for the Namibian context and the components of digital health, innovation and digital ecosystems identified in literature. The essential components identified will inform decision makers in the Namibian healthcare sector on the implementation of a digital health innovation ecosystem for Namibia.